The Influence of Locus Of Control and Resonant Leadership on Teacher Performance through Teacher Work Engagement in Gaung Anak Serka District - Sri Zuwefa; Syaifuddin Syaifuddin; Salman Faris (Jurnal of Management and Social Sciences, 2023)
This study aims to determine the effect of Locus of Control and Resonant Leadership on Elementary School Teacher Performance in Gaung Anak Serka District, Indra Hilir Regency, Riau. The number of samples in this study were 134. The techniques used to collect data were questionnaires and interviews. The results showed that 1. locus of control (X1) did not significantly influence work engagement (Y). 2. Directly there was a significant influence of resonant leadership (X2) on work engagement (Y). There is no direct significant effect of the locus of control variable (X1) on teacher performance (Z). 4 There is a direct significant effect of the resonant leadership variable (X2) on teacher performance (Z). 5. There is a direct significant effect of work engagement (Y) on teacher performance (Z). 6. Work engagement is not significant mediating locus of control on teacher performance. Work engagement significantly mediates resonant leadership on teacher performance.